Assessment of radionuclide dispersion and radiation dose for a hypothetical VVER-1200 accident in Zimbabwe - Chiyangwa. S.; Birikorang. S.A.; Agbodemegbe. V.Y. (Annals of Nuclear Energy, 2025)
The potential introduction of a VVER-1200 nuclear reactor in Zimbabwe to meet the growing energy demands requires a thorough understanding of its radiological safety and environmental impacts. To address this concern, a detailed simulation and analysis was conducted for a hypothetical VVER-1200 nuclear reactor at Lake Kariba, focusing on a design basis loss of coolant accident (LOCA). The study utilized site-specific meteorological data for both the wet and dry seasons to model the dispersion of radioactive materials using the RASCAL 4.3.4 code. The health effects of the radiological accident were quantified using dosimetric quantities, specifically the Total Effective Dose Equivalent (TEDE) and Child Thyroid Committed Effective Dose (CTCED), which are crucial for evaluating the effectiveness of emergency mitigation actions such as evacuation, sheltering-in-place, and the administration of prophylactic potassium iodide (KI) as a thyroid blocking agent. The results revealed that the doses during the wet season were approximately three times higher than those in the dry season, with the maximum TEDE reaching 153 mSv at 0.16 km from the release point during the wet season, compared to 45.5 mSv during the dry season under the containment leakage release pathway. The study also showed that both TEDE and CTCED were significantly higher near the release point and decreased as the distance downwind increased. Beyond a radius of 16.09 km (10 miles) from the release point, doses fell below 1 mSv, making this region safe for the public except under the worst-case scenario during the wet season, where doses as high as 50.2 mSv were observed at the 16.09 km distance. These findings underline the need for robust emergency preparedness and response plans, tailored to the specific climatic conditions of the region. The study provides critical baseline data that can assist decision-makers and regulators in developing regulations and guidelines to ensure adequate protection of the public and the environment in the event of a radiological accident.
Research Article
Keywords: LOCA; Source term; TEDE